PENGARUH PERILAKU BULLYING TERHADAP MINAT BELAJAR SISWA DI SMP NEGERI 7 MUARO JAMBI - Auldila, Pebri; Rasimin, R; Rahmayanty, Dinny (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
The aim of this research is to see whether there is an influence of bullying behavior on students' interest in learning at SMP N 7 Muaro Jambi. This type of research is quantitative research using the ex post facto method. The population in this study were students in grades VIII A - VIII G. The sample in this study was students who had been victims of bullying and had low interest in learning, consisting of grades VIII A to VIII G, totaling 41 students. The instrument used in this research is a questionnaire and the measurement scale used in this research is the Likert scale. Furthermore, in the statistical assumption test, there are two conditions that must be fulfilled, namely the data normality test and the data linearity test, and this research uses a simple regression analysis technique to measure the influence of bullying behavior (X) on variable learning interest (Y) with the help of SPSS version 23 . The results of this study show that the determination is at 0.146 or 14.6%. The criteria for interpreting the influence of determination of 0.146 or 14.6% are in the low but certain category (0.05 – 0.16), so this research shows that there is a significant influence between the bullying variable (X) on interest in learning (Y).